Prevention of Nausea and Vomiting in Patients Undergoing Oral Anticancer Therapies for Solid Tumors. (3rd September 2015) - Costa, Ana Lúcia; Abreu, Catarina; Pacheco, Teresa Raquel; Macedo, Daniela; Sousa, Ana Rita; Pulido, Catarina; Quintela, António; Costa, Luís
Abstract : Chemotherapy-induced nausea and vomiting (CINV) is still a common and debilitating side effect despite recent advances in its prevention and treatment. The intrinsic emetogenicity of chemotherapy agents allowed grouping into four risk groups (high, moderate, low, and minimal risk of emetogenicity). The prevention of acute and delayed CINV for intravenous agents and one day regimens is well studied, although, there are few data about management of CINV induced by oral cytotoxic agents and targeted therapies, usually administered in extended regimens of daily oral use. Until now treatment of nausea and vomiting caused by oral antineoplastic agents remains largely empirical. The level of evidence of prophylactic antiemetics recommended for these agents is low. There are differences in the classification of emetogenic potential of oral antineoplastic agents between the international guidelines and different recommendations for prophylactic antiemetic regimens. Herein we review the evidence for antiemetic regimens for the most used oral antineoplastic agents for solid tumors and propose antiemetic regimens for high to moderate risk and low to minimal risk of emetogenicity.